Non-neoformans cryptococcemia in a patient with hodgkin’s lymphoma - Ding, Chuanhun; Kamarudin, Norhidayah (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Cryptococcemia attributed to non-neoformans cryptococci has not received much attention due to the relative scarcity of reported cases. The primary aim of this case report is to highlight several notable characteristics of Cryptococcus laurentii. A 35-year-old woman presented with a right supraclavicular mass and a history of low-grade fever. A yeast was isolated from her blood. It formed cream-colored colonies which turned yellowish after 72 h of incubation and had a microscopic morphology of elongated budding yeast cells. Its identity was confirmed to be C. laurentii through carbohydrate assimilation testing (ID 32 C). The patient responded clinically to fluconazole and cleared the cryptococcemia. She was subsequently diagnosed with Hodgkin’s lymphoma through histopathological examination of the supraclavicular mass